2022
DOI: 10.1177/14759217221077612
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness identification method for asphalt pavement layers and interfaces using monitoring data from built-in sensors

Abstract: The bearing capacity of asphalt pavement gradually deteriorates due to repeated traffic loads. As the crucial mechanical index to evaluate the bearing capacity, the evolution of the stiffness of pavement layers and interfaces is necessary to be mastered. This paper proposes a stiffness identification method for the asphalt pavement layers and interfaces by using monitoring data from built-in sensors. First, the analytical solution of multi-layered elastic/viscoelastic medium with imperfect interlayer subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Most of the studies where factors that impact asphalt pavements durability are identified mainly focus on (1) traffic effects and vehicular loads, (2) characteristics and properties of the materials that make up the structure of the pavements, and (3) weather and road operation effects [4]. Under the coupled action of traffic and environmental effects, asphalt binders undergo significant physical changes such as aging, healing, and premature failure due to their sensitivity to temperature and loading rate, resulting in the early deterioration of asphalt pavement performance [5][6][7]. The climatic factors that affect the performance of asphalt pavements include high temperature, low temperature, water, fatigue, and aging [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies where factors that impact asphalt pavements durability are identified mainly focus on (1) traffic effects and vehicular loads, (2) characteristics and properties of the materials that make up the structure of the pavements, and (3) weather and road operation effects [4]. Under the coupled action of traffic and environmental effects, asphalt binders undergo significant physical changes such as aging, healing, and premature failure due to their sensitivity to temperature and loading rate, resulting in the early deterioration of asphalt pavement performance [5][6][7]. The climatic factors that affect the performance of asphalt pavements include high temperature, low temperature, water, fatigue, and aging [8,9].…”
Section: Introductionmentioning
confidence: 99%